PELAKSANAAN PEMBINAAN NARAPIDANA DI LEMBAGA PEMASYARAKATAN KELAS II A BUKITTINGGI - Failin, Failin; Yuserlina, Anny (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
He importance of community participation in the process of developing prisoners. Prisoner development is an inseparable part of the law enforcement process. The correctional inmates to become complete human beings, realize their mistakes, improve themselves and not repeat criminal acts so that they can be accepted again by society, can play an active role in development and can live normally as good and responsible citizens. The correctional system functions to prepare correctional inmates so that they can integrate healthily with society, so that they can play their role again as free and responsible members of society. The legal basis for the existence of correctional institutions in Indonesia is contained in Law Number 22 of 2022 concerning Corrections. Keywods: Implementation, Development, Prisoners, Correctional Institutions